Bipolar growth model with investment flows - Filipowicz, Katarzyna; Misiak, Tomasz; Tokarski, Tomasz (Economics and Business Review, 2016)
The aim of the present study is to design a bipolar model of economic growth with investment flows between two types of economies (conventionally referred to as relatively rich economies and relatively poor economies). Therefore in the following considerations it is assumed that the process of capital accumulation depends on investments undertaken in the economy. At the same time the Solow growth model takes into account only investments financed by domestic savings, whereas in the bipolar growth model also the investment flows between rich and poor economies are considered. It is assumed that both relatively rich economies are investing in the relatively poor economies and the poor economies make investments in the rich economies. The paper analyses the long-term equilibrium of the growth model, both in terms of existence of steady states of the system of differential equations and in terms of the stability of a non-trivial steady state. What is more economic characteristics of the point of the long-term equilibrium of the model are examined, model parameters are calibrated and growth paths of basic mmacroeconomic variables in selected variants of numerical simulations are presented.